ANALISIS EFISIENSI BELANJA DAERAH DI KABUPATEN SUMBAWA (Studi Kasus Bidang Pendidikan dan Kesehatan) - Neneng Erlina Indriati (Universitas Negeri Malang, 2014)
This research aims to (i) describe the level of expenditures efficiency of education and health in the district of sumbawa (ii) knowing the Government's efforts to improve the efficiency of Sumbawa district on education and health expenditures. A method of research used are a case study with quantitative and qualitative approach. The measurement of the efficiency of the method using Data Envelopment Analysis (DEA). The research results show that (i) Occurring inefficiency on average, whether technical cost efficiency and technical system efficiency (ii) the Government's efforts to improve the efficiency of Sumbawa district on education and health expenditures are: (a) health sector, to overcome the shortage of medical personnel, with a horizontal reference, some clinics that become the reference horizontally, as satellite clinics, as well as empowerment of a Temporary Doctors and Temporary Midwives. (b) education sector, the ratio of teachers in each school who are relatively less, to anticipate, school are allowed to raise Temporary Teachers that be paid by the operational funds of the school. (c) Work zone or the subdivisions for packages of activities/programs so that the allocation of resources can be effectively and efficiently. And (d) Determination of scale of priorities, identification and synchronization of data on facilities and infrastructure. Keywords: education, health, efficiency, DEA